2020
DOI: 10.1002/aic.17054
|View full text |Cite
|
Sign up to set email alerts
|

Demand‐based optimization of a chlorobenzene process with high‐fidelity and surrogate reactor models under trust region strategies

Abstract: This work demonstrates the optimization of the industrial scale chlorobenzene process, which continuously produces multiple products and includes a multiphase reaction with bubble column reactors (BCRs). The trust region filter (TRF) method is applied to carry out the demand‐based optimization of large chlorobenzene process with high‐fidelity BCR models. The TRF method uses surrogate models that substitute the high‐fidelity BCR models in the process model, and avoids the direct implementation of high‐fidelity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…These ROMs are updated at each iteration of the TRF algorithm to ensure that they are accurate within a small trust region around the previous solution, obtained from the running the detailed discretised DAE model of Kazi et al (2020a). For more details on the TRF strategy, see the work of Yoshio and Biegler (2020). The NLP is solved at each iteration of the TRF, including all NLP subproblems, with the HEN NLP linked to the MEN and REN NLPs via the temperatures and flowrates of the lean streams in the MEN, which are also the flowrates of the rich streams in the REN.…”
Section: Detailed Network Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…These ROMs are updated at each iteration of the TRF algorithm to ensure that they are accurate within a small trust region around the previous solution, obtained from the running the detailed discretised DAE model of Kazi et al (2020a). For more details on the TRF strategy, see the work of Yoshio and Biegler (2020). The NLP is solved at each iteration of the TRF, including all NLP subproblems, with the HEN NLP linked to the MEN and REN NLPs via the temperatures and flowrates of the lean streams in the MEN, which are also the flowrates of the rich streams in the REN.…”
Section: Detailed Network Optimisationmentioning
confidence: 99%
“…(Kazi et al, 2020b). More recently, Kazi et al (2020c) developed a novel algorithm for including these models into HENS as surrogates via a TRF algorithm from Yoshio and Biegler (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work uses, e.g., artificial neural networks to set up a surrogate model enabling multi-scale optimization exemplified with a membrane process [91] or thin film growth processes [92]. Other solutions proposed to deal with multiscale problems are model reduction methods or surrogate modeling approaches to reduce computational effort for complex nonlinear systems to allow for efficient control and scheduling [93][94][95][96]. Some aspects concerning the abovementioned challenges are expected to be treated using machine learning methods in chemical engineering in the future [97].…”
Section: Future Challengesmentioning
confidence: 99%
“…Nevertheless, chlorobenzene remains widely applicable in many fields such as rubber, plastics, pharmaceuticals, dyes, and pigments. On the other hand, dichlorobenzene is used as a precursor for the production of paints and coatings and has applications in electronics and agrochemicals industries [1]. Dorota et al found that the solubility of N-alkylated naphthalene diimides (NDI) in dichlorobenzene or chloroform was highest for NDIC5-NDIC8, i.e., medium-length alkyl chains NDI which are used in electronics, photovoltaics, and sensors [2].…”
Section: Introductionmentioning
confidence: 99%